Caregiver Experiences With an Innovative Farmers' Market Incentive Program for Children in Flint, Michigan - Amy Saxe-Custack PhD, MPH, RD; Heather Claire Lofton PhD; Mona Hanna-Attisha MD, MPH, FAAP; Zachary Tata MPH; Tiffany Ceja MSE; Jenny LaChance MS, CCRC (SAGE Publishing, 2019)
An innovative farmers' market incentive program designed specifically for children was implemented to address persistent challenges with accessing fresh, nutrient-rich foods in a food desert community. The current study sought to qualitatively examine caregiver perceptions of the incentive program. Following distribution of farmers' market incentives to all children (ages 0 to 15 years) at 43 Flint-area early childcare facilities and elementary schools, researchers conducted semistructured interviews with 37 caregivers (mean age = 39.59 ± 11.73 years). The majority were female (87%) and African American (53%). Through these interviews, researchers explored family experiences with the farmers' market incentive program, as well as changes in environmental factors that may have resulted from program participation. Interviews were audio recorded and transcribed verbatim for textual analysis. Thematic analysis was used to identify patterns across transcripts and formulate emerging themes. Four recurrent themes emerged during interviews: (1) fruit and vegetable access, (2) child influence, (3) autonomous grocery shopping, and (4) program expansion. Interview participants indicated that the farmers' market incentive program was an effective tool to both encourage families to visit the farmers' market and purchase fresh foods there. Program design, particularly distribution to children, was credited with introducing families to the local farmers' market. The current study suggests that a farmers' market incentive program targeting children who reside in a food desert community may have meaningful impacts on access to fresh, nutrient-rich foods.